2018
DOI: 10.1021/acs.macromol.7b02279
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Cylinder Morphologies with 10 nm Scale Periodicity in Biomass-Based Block Copolymers

Abstract: Microphase-separated structures of block copolymers (BCPs) have attracted considerable attention for their potential application in the bottom-up fabrication of 10 nm scale nanostructured materials. To realize sustainable development within this field, the creation of novel BCP materials from renewable biomass resources is of fundamental interest. Thus, we herein focused on maltoheptaose-b-poly(δdecanolactone)-b-maltoheptaose (MH-b-PDL-b-MH) as a sustainable alternative for nanostructure-forming BCPs, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In general, characteristic and useful properties of block copolymers are attributable to the linkage between segments with contrasting properties, such as soft and hard segments ( Lendlein et al, 1998 ). In fact, studies on chemically synthesized block copolymers typically select segments with distinct structures; for example, polyester and polysaccharide segments ( Isono et al, 2018 ). PHAs were also chemically conjugated with PHAs ( Dai et al, 2009 ) and/or other types of polymers, such as poly(ε-caprolactone), to improve the flexibility of the material ( Saad et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, characteristic and useful properties of block copolymers are attributable to the linkage between segments with contrasting properties, such as soft and hard segments ( Lendlein et al, 1998 ). In fact, studies on chemically synthesized block copolymers typically select segments with distinct structures; for example, polyester and polysaccharide segments ( Isono et al, 2018 ). PHAs were also chemically conjugated with PHAs ( Dai et al, 2009 ) and/or other types of polymers, such as poly(ε-caprolactone), to improve the flexibility of the material ( Saad et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…δ-dodecalactone, 28 PEG and ω-pentadecalactone, 29 lactide, 30 methylene diphenyl diisocyanate, 10 1,4 butylene oxide, 14 δ-valerolactone 31 and maltohepotaose. 32 δDL occurs naturally in fruits 33 and milk, 34 but can also be produced enzymatically on large scale from fatty acids and essential oils. 35,36 Recently, it was shown that catalytic transfer hydrogenation 37 could be a new and interesting course to synthesize the monomer, which also increases the potential of establishing δDL as a biobased platform monomer.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous investigations, we have found that oligosaccharides are useful building blocks for designing BCPs capable of self-assembling into microphase-separated structures of sub-10 nm domain size [36][37][38][39][40][41]. In these systems, the strong hydrophilicity imparted by the presence of multiple hydroxyl groups results in oligosaccharide-containing amphiphilic BCPs with high χ values, and the rigidity of the carbohydrate backbone further enhances the incompatibility of the hydrophilic block with the hydrophobic block.…”
Section: Introductionmentioning
confidence: 99%